2021
DOI: 10.11648/j.ep.20210501.11
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Due to Non-magnetic Disorder in 2D Anisotropic d-wave High T<sub>c</sub> Superconductors

Abstract: Inspired by the studies on the influence of transition metal impurities in high Tc superconductors and what is already known about nonmagnetic suppression of T c in unconventional superconductors, we set out to investigate the behavior of the nonmagnetic disordered elastic scattering for a realistic 2D anisotropic high T c superconductor with line nodes and a Fermi surface in the tight-binding approximation. For this purpose, we performed a detailed self-consistent 2D numerical study of the disordered averaged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…It resembles a gapless node points in unconventional superconductors (also it resembles the line nodes points model of high T c compounds we previously calculated for La 2−x Sr x CuO 4 in Ref. [29]). This intuitively means that the half filling ground state in the unitary limit gives point nodes and a flat dispersion law if the TB parameters are appropriately chosen.…”
Section: The Unitary Limit For the Case Of Nodalsupporting
confidence: 74%
See 1 more Smart Citation
“…It resembles a gapless node points in unconventional superconductors (also it resembles the line nodes points model of high T c compounds we previously calculated for La 2−x Sr x CuO 4 in Ref. [29]). This intuitively means that the half filling ground state in the unitary limit gives point nodes and a flat dispersion law if the TB parameters are appropriately chosen.…”
Section: The Unitary Limit For the Case Of Nodalsupporting
confidence: 74%
“…However, as we recently reported [20], Born scattering does not play a role in the low temperature properties of Sr 2 RuO 4 it has a RPS window of ∆ 0 = 1.0 meV. At this point we also emphasize, that for the case of the lines nodes superconductor La 2−x Sr x CuO 4 , we reported that this compound can be numerically be in the Born limit with a RPS scattering window if ∆ 0 = 33.9 meV, for it we found another family of Wigner probabilistic distributions [20,29].…”
Section: Non-magnetic Impurity Scattering the Edwards-nambu-gorkov Fo...supporting
confidence: 66%
“…First we vary the inverse strength parameter c from 0 to 1 and second, we vary the value of the parameter Γ + from optimal to dilute doping in the function ω ω + i 0 + ). We finish our short report by comparing our findings with a line nodes tight binding analysis for High Tc compounds recently investigated using the same approach [18].…”
Section: Introductionmentioning
confidence: 77%
“…= (0.2, 0.4) meV and an electron-hole (eh) symmetry * , = + − , − . The order parameter corresponds to the supercoducting gap Δ , = Δ -, with an irreducible representation basis function -, = %cos − cos ) and the zero gap parameter Δ = 33.9 meV [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since our primary goal is to visualize and describe briefly some properties of the three family of Wigner probabilistic distributions, we ought to emphasize that the whole analysis relays on the calculation of the function [9].…”
Section: Introductionmentioning
confidence: 99%